Substitution between Groups of Highly-Educated, Foreign-Born, H-1B Workers - Chad Sparber (Institute of Labor Economics (IZA), 2018)
Highly-educated foreign-born workers can secure legal US employment through the H-1B program. The annual cap on H-1B issuances varies across individuals' US educational experience, H-1B work history, and employer type. Caps are met quickly in most but not all years. This paper exploits these differences to identify whether firms substitute across different sources of highly-educated, foreign-born, H-1B labor. New H-1B workers without advanced degrees from US universities substitute with new H-1B workers possessing advanced US degrees. We find no evidence for substitution with established H-1B workers.
Keywords: J61; F22; 330; skilled workers; H-1B status; immigrant